Antitumor activity of a novel Aurora A/B kinases inhibitor TY-011 against gastric cancer by inducing DNA damage. Issue 5 (June 2020) - Jiang, Tongtong; Liu, Wang; Lu, Yu; Fang, Yanfen; Chen, Rui; Zhang, Wanli; Liu, Xuan; Zhang, Xiongwen
Abstract : TY-011, a novel Aurora A/B kinases inhibitor, was found in our previous study to exhibit prominent inhibitory effects on growth of gastric cancer, both in vitro and in vivo . To clarify the mechanisms of TY-011 in inhibiting proliferation of gastric cancer cells, the effects of TY-011 on mitosis, cell cycle, apoptosis and cellular DNA were checked in the present study. Our results showed that TY-011 treatment induced aberrant mitosis, G2/M phase arrest and apoptosis. Importantly, TY-011 induced evident DNA damage in MGC-803 and MKN-45 human gastric cancer cells, which was further characterized as DNA double-strand break. Furthermore, cells treated with TY-011 appeared to generate multiple spindle fibers emanating from several spindle poles, leading to poly-merotelic kinetochore. These results suggested that TY-011 induced abnormal microtubule-kinetochores attachment and thus DNA damage, apoptosis and finally inhibition of cell proliferation of human gastric cancer cells.